2014
DOI: 10.1111/jgh.12601
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and safety of endoscopic treatment for nonampullary duodenal adenoma and adenocarcinoma

Abstract: Endoscopic treatment is minimally invasive management for duodenal adenomas and superficial adenocarcinomas. It would be helpful for medical doctors in the management of duodenal neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Basically, incidence of complications after ER for SNADETs was significantly higher than that in any other part of the digestive tract [15,25,26]. This is due to the anatomical features, which include the following: a narrow lumen; a precipitous flexure that causes poor stability of the endoscope; Brunner's glands in the submucosal layer that stiffen the duodenal wall, resulting in poor mucosal lifting; a thin muscle layer that results in a higher incidence of intraoperative perforation and increased risk of other complications such as postoperative bleeding and delayed perforation; and difficult access if emergency surgery becomes necessary [2,9,27]. Risk of intraoperative and delayed perforation was reported not based on location of SNADETs but on the tumor size [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, incidence of complications after ER for SNADETs was significantly higher than that in any other part of the digestive tract [15,25,26]. This is due to the anatomical features, which include the following: a narrow lumen; a precipitous flexure that causes poor stability of the endoscope; Brunner's glands in the submucosal layer that stiffen the duodenal wall, resulting in poor mucosal lifting; a thin muscle layer that results in a higher incidence of intraoperative perforation and increased risk of other complications such as postoperative bleeding and delayed perforation; and difficult access if emergency surgery becomes necessary [2,9,27]. Risk of intraoperative and delayed perforation was reported not based on location of SNADETs but on the tumor size [23].…”
Section: Discussionmentioning
confidence: 99%
“…Superficial non-ampullary duodenal epithelial tumors (SNA-DETs) are defined as sporadic adenoma and adenocarcinoma that are confined to the mucosa or submucosa that do not arise from the ampulla of Vater [1]. Because of the rarity of SNADETs [2], their etiology, prevalence, and risk factors remain unknown. It was reported that SNADETs were detected using esophagogastroduodenoscopy (EGD) in adult patients at a rate of 0.1 % to 0.3 % [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of a duodenal injury associated with percutaneous kidney access gaining was well described so far and ranged from surgical options including laparotomy to conservative, with prolonged fasting up to 14 days, parenteral hyperalimentation, and prolonged hospital stay [5, 6]. Despite the fact that the location of the duodenal defect directed our surgical team towards open surgery experience of our endoscopist, who is managing duodenal adenocarcinoma endoscopically [7] and the size of the defect was taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed perforation is a rare (0.4% 7 ), but serious, complication of colorectal ESD, possibly requiring emergency surgery. The intraoperative perforation rate of duodenal ESD was reported to range from 6.3% to 75%, [25][26][27][28] and delayed perforation of duodenal ESD may require emergency surgical treatment or cause a negative clinical course. Therefore, the prevention of postoperative perforation is important.…”
Section: Introductionmentioning
confidence: 99%